Persepsi Masyarakat terhadap Penerapan Prinsip Ketahanan Pangan Berbasis Hukum dan Ekonomi di Desa Rias Kecamatan Toboali (Indonesian Version) - Dhea Nurisma; Efendi Sugianto; Rahmiati Ranti Pawari; Nur Naini Muna; Nora Rahma Aprilika; Gea Andini; Meylie Cawla; Reo Pratama; Eduar Saputra; Jumaiyeh Jumaiyeh; Ihsan Naluri; David Robertino (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze community perceptions of the application of legal and economic principles of food security in Rias Village, Toboali District. Food security is a crucial issue because it is directly related to survival, welfare, and regional economic stability. However, the community's understanding of food security is often limited to food availability, without considering its relationship with legislation and the dynamics of the village economy. The research method used was qualitative with a descriptive approach that included in-depth interviews, observation, and documentation of the local community. The results of the study show that the people of Rias Village have a positive perception of the importance of food security, especially from an economic perspective, such as market access, food prices, and business capital. However, understanding of legal aspects is still limited, especially regarding government and local regulations that should protect the community's right to access food. This perception confirms that the successful implementation of food security principles in Rias Village is influenced by legal policies that favor the community and economic strategies that encourage local food self-sufficiency.